1997
DOI: 10.1023/a:1018546730925
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Natural self-reinforced composite, bamboo, was surface modified by phosphorylation with urea-H3PO4 and NaOH-H3PO4 methods; then precalcification was performed by immersing samples in saturated Ca(OH)2 solution. After that, calcium phosphate can be formed on the surface of bamboo samples in calcification media: simulated body fluid (1.5 SBF) and accelerated calcification solution (ACS). Experimental results reveal that pre-calcification is an inevitable step for the formation of calcium phosphate. The calcium p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…It has been observed by several investigators that functionalized polymers with surface bound phosphate group induces in vitro nucleation of calcium phosphate crystals on their surface under simulated physiological environment. 33–35 However, many of these surface functionalized polymers require pretreatments such as calcium hydroxide/calcium chloride pretreatment after functionalization for the in vitro mineralization of calcium phosphate. Moreover the popular surface phosphorylation techniques are done at higher temperature (<100°C), using organic solvents and catalysts, which may alter the basic polymer characteristics significantly.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed by several investigators that functionalized polymers with surface bound phosphate group induces in vitro nucleation of calcium phosphate crystals on their surface under simulated physiological environment. 33–35 However, many of these surface functionalized polymers require pretreatments such as calcium hydroxide/calcium chloride pretreatment after functionalization for the in vitro mineralization of calcium phosphate. Moreover the popular surface phosphorylation techniques are done at higher temperature (<100°C), using organic solvents and catalysts, which may alter the basic polymer characteristics significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic calcium phosphates generally induce the formation of an apatite layer in simulated plasma solutions. Some other synthetic biomaterials have also shown the capability of inducing the formation of an apatitic mineral, namely polymers containing phosphate functionalities,35–38 including phosphorylated cellulose derivatives 39–41. However, only low degrees of phosphorylation were used because of the lack of techniques that would allow highly phosphorylated products to be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, surface phosphorylation has been identified as an effective method for surface functionalization [117119]. Varma et al demonstrated formation of calcium phosphate coating on chitosan by direct phosphorylation while PMMA required surface functionalization by coupling with ATP molecule elicit HAP coating [120].…”
Section: Biomimetic Mineralizationmentioning
confidence: 99%
“…Surface phosphorylated poly(vinyl alcohol), PVA exhibited enhanced cytocompatibility in vitro in addition to substantial apatite coating [121]. Instead of urea-phosphoric acid method, Li et al [117] employed sodium hydroxide-phosphoric acid for phosphorylating bamboo while Granja et al [122] phosphorylated regenerated cellulose with the aid of phosphoric acid and triethyl phosphate. In another study, the authors presented an alternative way for surface phosphorylation illustrated with poly (hydroxyl ethyl methacrylate-co methyl methacrylate) for biomimetic growth of calcium phosphate [119], and the functionalized material was demonstrated to direct bone bonding and elicited new bone formation [118].…”
Section: Biomimetic Mineralizationmentioning
confidence: 99%